Ameliorative Effects of Different Transcranial Electrical Stimulation Paradigms on the Novel Object Recognition Task in a Rat Model of Alzheimer Disease: - Zarifkar, Amir Hossein; Zarifkar, Asadollah; Nami, Mohammad; Rafati, Ali; Aligholi, Hadi; Vafaee, Farzaneh (Galen Medical Journal, 2019)
Background: Treatment of Alzheimer as a disease that is associated with cognitive impairment has been associated with some restrictions. Recently, researchers have focused on non-pharmacological treatments, including non-invasive stimulation of the brain by transcranial electrical stimulation (tES). Four main paradigms of transcranial electrical current include transcranial direct current stimulation (tDCS), transcranial alternative current stimulation (tACS), transcranial random noise stimulation (tRNS), transcranial pulse current stimulation (tPCS). The tDCS is a possible new therapeutic option for patients with cognitive impairment, including Alzheimer disease. Materials and Methods: The study was done on Sprague-Dawley male rats weighing 250-270 g. to develop Alzheimerâ€™s model, the cannula was implanted bilaterally into the hippocampus. AÎ² 25-35 (5Î¼g/ 2.5Âµl/day) was microinjected bilaterally for 4 days. Then, an electrical stimulation paradigm was applied to the animal for 6 days. Animal cognitive capacity was evaluated on day 11 and 12 by novel object recognition (NOR) test. Results: Our results showed that application of tDCS; tACS; tRNS and tPCS reversed beta-amyloid-induced impairment (P<0.05). The tRNS Group spent total exploration time around the objects compared to other groups (P<0.05). There was no significant difference between the four different paradigms in discrimination ratio and the percentage of total exploration time. Conclusion: The results of this study showed that the use of multiple sessions of different tES paradigms could improve AÎ²-induced memory impairment in the NOR test. Therefore, based on evidence, it can be expected that in addition to using tDCS, other stimulatory paradigms may also be considered in the treatment of AD. [GMJ.2019;8:e1440]